Recent Progress on Atomic Spectroscopy of Highly Ionized Ions in Laboratory Plasmas for Fusion Research - Morita, S.; Oishi, T.; Zhang, L.; Dong, C. F.; Huang, X. L.; Zhang, H. M.; Goto, M. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2023)
Magnetic dipole forbidden (M1) transitions have been observed for highly ionized Ar, Kr, Mo and Xe ions in LHD. It was found that the M1 transition is observable if the spontaneous emission coefficient is larger than \(\sim10^{2}\) s\({}^{-1}\). An intensity ratio of M1 transition to electric dipole (E1) transition was analyzed for F-like TiXIV by assuming the presence of monoenergetic 90 keV protons originated in neutral beams for plasma heating. An effect of 3.52 MeV alpha (He\({}^{2+}\)) particle collision was also theoretically examined for F-like MoXXXIV and XeXLVI. We found the XeXLVI intensity can be affected by roughly 10% if the alpha particle density is one percent to the electron density. L\(α\) \((n=3\)-\(2)\) transitions of FeXVII-XXIV were observed at 10-18 A in LHD. Measured intensity ratios among Ne-like FeXVII lines are examined against \(T_e\) and \(n_e\), and compared with theoretical values. An influx rate of W\({}^{6+}\) ions was determined to be \(Γ_W=6×10^{11}\) cm\({}^{-2}\) s\({}^{-1}\) from the intensity of WVII which was identified at 216.2 A and 261.4 A in HL-2A. Densities of W\({}^{43+}\) and W\({}^{45+}\) ions were analyzed and found to be an order of \(10^{8}\) cm\({}^{-3}\) based on the radial profile measurement of WXLIII-XLVI at 120-134 A in EAST. Several tungsten spectra from low ionization stages, WIV-VII, were identified in LHD at VUV range of 500-1500 A and the ion temperature was determined from the Doppler broadening, e.g. T\({}_{i}\)(WVI)\(=\)137\(±\)52 eV.